Everything must go : the stories we tell about the end of the world - Lynskey, Dorian (Pantheon Books, 2024)
A rich, captivating, and darkly humorous look into the evolution of apocalyptic thought, exploring how film and literature interact with developments in science, politics, and culture, and what factors drive our perennial obsession with the end of the world. As Dorian Lynskey writes, "People have been contemplating the end of the world for millennia." In this immersive and compelling cultural history, Lynskey reveals how religious prophecies of the apocalypse were secularized in the early 19th century by Lord Byron and Mary Shelley in a time of dramatic social upheaval and temporary climate change, inciting a long tradition of visions of the end without gods. With a discerning eye and acerbic wit, Lynskey examines how various doomsday tropes and predictions in literature, art, music, and film have arisen from contemporary anxieties, whether they be comets, pandemics, world wars, the Cuban Missile Crisis, Y2K, or the climate emergency. Far from being grim, Lynskey guides readers through a rich array of fascinating stories and surprising facts, allowing us to keep company with celebrated works of art and the people who made them, from H.G. Wells, Jack London, W.B. Yeats and J.G. Ballard to The Twilight Zone, Dr. Strangelove, Mad Max and The Terminator. Prescient and original, Everything Must Go is a brilliant, sweeping work of history that provides many astute insights for our times and speaks to our urgent concerns for the future-- Provided by publisher.